Does the way we do science foster discovery? - Sivadas, Nithin (Frontiers in Astronomy and Space Sciences, 2023)
Freedom to explore the unknown is key to scientific discovery. Maximizing modern individualistic measures of scientific productivity like the number of citations and publications may impede the progress of science as a whole.